Spatial distribution, dispersal behavior and population structure of Tribolium castaneum herbst (Coleoptera: tenebrionidae) - Semeao, Altair Arlindo (Kansas State University, 2011)
Knowledge of factors influencing the establishment, persistence and distribution of stored-product pests aids the development of effective Integrated Pest Management (IPM) programs in food storage and processing facilities. This research focused primarily on Tribolium castaneum, which is one of the most important pests of mills. Populations of T. castaneum from different food facilities can potentially be interconnected by either their own dispersal behavior or by human transportation. Population genetic structure analyses based on microsatellites and other insertion-deletion polymorphisms (“indels”) showed that populations from different mills around the US are genetically distinct from each other, but the level of differentiation was not correlated with the geographic distance. A potential source of insect infestation within a food facility is spillage that accumulates outside or movement from bulk storage facilities on site. Results from three facilities showed that most stored-product species were captured both inside and outside buildings, but T. castaneum was rarely captured outside of the facilities. Spatial distribution of all species outside was associated with the proximity of buildings, not necessarily with areas with accumulated spillage. T. castaneum populations inside facilities are potentially exposed to frequent genetic bottlenecks resulting from structural fumigations. Changes in allele frequencies through time, based on the analysis of microsatellites and other indels in individuals collected in a mill, confirmed bottleneck effects. To understand how spatial distribution of T. castaneum within a mill could be influenced by environmental and physical factors, a range of variables were measured at each trap location. There was significant variation among trap locations regarding beetle captures and the variables measured, but increase in beetle captures correlated only with increase in temperature and spillage production. Tribolium castaneum response to visual cues could influence attraction to pheromone and kairomone olfactory cues used in traps. Results of laboratory experiments showed that adults respond to tall narrow black shapes and placing traps in front of these shapes can increase captures. This research provides new insights into factors influencing the spatial distribution of T. castaneum and could help in improving monitoring programs for this important pest of the food industry.
Keywords: Tribolium castaneum; Spatial distribution; Population structure; stored-product insects; Agriculture, Agronomy (0285); Biology, Entomology (0353)